Wearable resistance training for speed and agility - Cleary Dolcetti, J.; Cronin, J. B.; Macadam, P.; Feser, E. H. (Strength and Conditioning Journal, 2019)
There are many training tools available to the coach for the improvement of speed and agility. This article discusses the use of wearable resistance (wr) and its place in the conditioning continuum. In terms of specific strength training and transference of adaptation to speed and agility, wr training is a bona fide contributor and can make a real difference to athleticism and competition performance. However, the utilization of wr training is embryonic; therefore, the focus of the article is on enhancing understanding and providing generic guidelines that can be translated across multiple movement patterns and sporting situations.